Relationship between pretracheal and/or prelaryngeal lymph node metastasis and paratracheal and lateral lymph node metastasis of papillary thyroid carcinoma: A meta-analysis - Wang, Bin; Zhu, Chun-Rong; Liu, Hong; Yao, Xin-Min; Wu, Jian (Frontiers in Oncology, 2022)
Objective We conducted a meta-analysis to study the relationship between pretracheal and/or prelaryngeal lymph node metastasis and paratracheal and lateral lymph node metastasis in papillary thyroid carcinoma. Method A systematic literature search was conducted using PubMed, Embase, and the Cochrane Library electronic databases for studies published up to February 2022. The reference lists of retrieved articles were also reviewed. Two authors independently assessed the methodological quality and extracted the data. A random-effects model was used to calculate the overall pooled relative risk. Publication bias in these studies was evaluated using Egger’s test and Begg’s test. Results Twenty-five independent studies involving 10,525 patients were included in the meta-analysis. The pooled relative risk for ipsilateral and contralateral paratracheal lymph node metastasis was 3.01 (95% confidence interval [CI]: 1.66, 5.45) and 5.68 (95% CI: 2.50, 12.88), respectively, in patients with pretracheal lymph node metastasis. Among patients with prelaryngeal lymph node metastasis, the pooled relative risk for ipsilateral paratracheal and/or pretracheal contralateral paratracheal, and lateral lymph node metastasis was 2.02 (95% CI: 1.90, 2.14), 2.22 (95% CI: 1.34, 3.67), and 3.85 (95% CI: 2.89, 5.14), respectively. Conclusion Pretracheal lymph node metastasis and prelaryngeal lymph node metastasis were significantly associated with an increased likelihood of both ipsilateral lymph node metastasis and contralateral paratracheal lymph node metastasis in papillary thyroid carcinoma. Prelaryngeal lymph node metastasis was positively correlated with the incidence of lateral lymph node metastasis.